Analisis Produktivitas Dump Truck Pada Storage Alternative Fuel And Raw Material Dengan Metode Cycle Time - Reza Ananda Putri; Tri Andi Setiawan; Aditya Maharani (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
This research reviews the planning and implementation of alternative fuel facilities at PT. Semen Gresik Rembang Factory, with a focus on storage and transportation efficiency of alternative fuels using the cycle time calculation method. This new facility is designed to increase the efficiency and smoothness of the cement production process, especially in the use of Alternative Fuel and Raw Material (AFR). By applying cycle time calculations, the time required to transport product waste from storage to the apron belt feeder with a dump truck can be determined more precisely. The results of the research show that the time required to use product waste in storage is 12 days, with a total cycle time from storage to apron of 16.68 minutes (0.3 hours) and requires 2 dump trucks to meet the needs of the apron belt feeder in one shift. The implementation of this method is expected to expedite the production process and increase operational efficiency at the Semen Gresik Plant Rembang Factory.